Toronto - Johnson, Lorraine; Hopkinson, Barbara (DK eyewitness top 10 travel guides., 2015)
Provides background information on Toronto. Recommends the 10 best restaurants, bars, nightlife, neighborhoods, hotels, and local attractions.